PRE-SERVICE ENGLISH TEACHERS' ATTITUDES TO CO-TEACHING - Iryna Zadorozhna; Olha Datskiv; Valentyna Shepitchak (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The purpose of this paper is to investigate pre-service English teachers' attitudes to co-teaching as a professional development tool and a collaboration method. Two instructors co-taught an undergraduate English Language Teaching Methodology course to gain experience and to model this method for pre-service English teachers. 60 students of Ternopil Volodymyr Hnatiuk National Pedagogical University, Department of Foreign Languages, participated in the study for one semester. Research instruments used in the study are students' reflective journals, focus groups discussions, and a survey. The students wrote regular entries in reflective journals after each session, participated in focus groups discussions, and filled out a survey at the end of the semester. It was hypothesised that co-teaching would engage learners and enhance their learning, help pre-service teachers to develop professionally, and serve as a model of effective instructional technique for their future teaching assignment. Results indicate the effectiveness of co-teaching in achieving these tasks. We also conclude that co-teaching in pre-service teacher education is an invaluable tool in developing teachers' and students' reflective skills and collaborative practices. The findings of the study can be applied in the design and implementation of educational programmes for pre-service foreign languages teachers.